Addressing MISEV guidance using targeted LC‐MS/MS: A method for the detection and quantification of extracellular vesicle‐enriched and contaminant protein markers from blood. Issue 9 (5th September 2022) - Newman, Lauren A.; Useckaite, Zivile; Rowland, Andrew
Abstract: Extracellular vesicles (EVs) are membrane‐bound nanosized particles released by cells into bodily fluids containing an array of molecular cargo. Several characteristics, including stability and accessibility in biofluids such as blood and urine, make EVs and associated cargo attractive biomarkers and therapeutic tools. To promote robust characterisation of EV isolates, the minimal requirements for the study of extracellular vesicles (MISEV) guidelines recommend the analysis of proteins in EV samples, including positive EV‐associated markers and negative contaminant markers based on commonly co‐isolated components of the starting material. Western blot is conventionally used to address the guidelines; however, this approach is limited in terms of quantitation and throughput and requires larger volumes than typically available for patient samples. The increasing application of EVs as liquid biopsy in clinical contexts requires a high‐throughput multiplexed approach for analysis of protein markers from small volumes of starting material. Here, we document the development and validation of a targeted liquid chromatography tandem mass spectrometry (LC‐MS/MS) assay for the quantification of markers associated with EVs and non‐vesicle contaminants from human blood samples. The assay was highly sensitive, requiring only a fraction of the sample consumed for immunoblots, fully quantitative and high throughput. Application of the assay to EVs isolated by size exclusion chromatography (SEC) and precipitation revealed differences in yield, purity and recovery of subpopulations.